Aqra Anticline: A Growing Structure in the Iraqi Kurdistan Region - Ghafur, Ala A.; Sissakian, Varoujan K.; Abdulhaq, Hawkar A.; Omar, Hassan O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Aqra Anticline is a double plunging anticline, oriented NW–SE with a steep southwestern limb and even overturned. Geomorphological features are interpreted using satellite images, as a result, it was found that the anticline shows clear geomorphological and structural features which indicate the lateral growth of the anticline. Among those features are water gaps, wind gaps, forked-shaped valleys, curved valleys, inclined valleys and dislocated and abandoned alluvial fans. Some of the vague interpreted features were checked and confirmed in the field.